Strengthening the knowledge base to respond to bean system priorities - Muthoni, Rachel; Muwanika, Roland; Tibalikwana, Mabel; Buruchara, Robin Arani (Pan-Africa Bean Research Alliance, 2012)
The Pan Africa Bean Research Alliance (PABRA) capacity building program contributes to the strengthening of the knowledge and skills of its partners. The capacity strengthening is geared towards improving service delivery; by equipping scientists and partners alike with the needed skills in technology development, delivery and decision making, and enhancing their potential to influence policies in their respective countries.